Microscopic Study of 5083-H321 Aluminium Alloy Under Fretting Fatigue Condition - Eslamian, Saeed (2005)
In this investigation, fretting fatigue study is carried out using 5083-H321 aluminium alloy. The test rig was designed to apply the normal load on the thickness side of the surface of the specimen, which is presumed to be the active surface for the fretting process. Fretting fatigue experiments were designed with an emphasis to study the crack initiation behaviour in the fretted region using scanning electron microscope. In order to investigate the possible crack initiation mechanisms in fretting fatigue as well as for the associated fatigue two different types of tests were proposed along with fundamental pure plain fatigue tests. These tests are named as fretting fatigue test and interrupted fretting fatigue test. First, pure plain fatigue tests were carried out with three maximum stresses of 200 MPa, 220 MPa, and 230 MPa, and with a stress ratio R of 0.1 at a frequency of 20 Hz. At each stress level three specimens were tested. Further fretting fatigue tests were carried out for normal pressures of 15 MPa, 30 MPa, and 45MPa at each axial stress level of 200 MPa, 220 MPa, and 230 MPa, with a stress ratio, R of 0.1 at a frequency of 20 Hz and. It has been found that the fatigue life reduces by a factor of 2.55, 3.48, and 3.54 for specimens tested with normal pressures of 15 MPa, 30 MPa, and 45 MPa using a maximum axial stress of 200 MPa respectively. The life reduces by factors of 3.16, 2.07, and 4.54 for specimens tested with normal pressures of 15 MPa, 30 MPa, and 45 MPa respectively using a maximum axial stress of 220 MPa. On the other hand the fatigue life reduces by a factor of 2.24, 2.37, and 2.81 for normal pressures of 15 MPa, 30 MPa, and 45 MPa respectively using maximum axial stress of 230 MPa. In general we can say that the fatigue life reduces by a factor of 2 to 3 for all specimens tested at fatigue stress levels and the normal pressures applied to the specimens as indicated above due to fretting fatigue in this investigation.